Effect of inverted orthoses on lower-extremity mechanics in runners - Williams, D. S.; McClay Davis, I.; Baitch, S. P. (Medicine & Science in Sports & Exercise, 2003)
INTRODUCTION: Foot orthoses are recommended for individuals with injuries associated with abnormal lower-extremity mechanics. However, the biomechanical effect of these devices is not completely understood. Most clinicians and researchers believe that foot orthoses are effective in reducing some aspect of rearfoot motion. This is important as many injuries are suggested to be the result of increased pronation. Inverted orthoses are a more aggressive treatment in those whose symptoms do not respond to standard orthotics. They are likely to alter motion in all planes. However, no three-dimensional studies have assessed lower-extremity mechanics in individuals wearing inverted orthotics. PURPOSE: The purpose of this study was to compare the three-dimensional kinematics and kinetics of the rearfoot and knee during running while varying orthotic intervention. METHODS: Eleven subjects were initially fitted with standard foot orthoses and then with inverted orthoses. Three-dimensional kinematic and kinetic data were collected for conditions of no orthoses, standard orthoses, and inverted orthoses. RESULTS: There were no differences between conditions in peak rearfoot eversion or rearfoot eversion excursion. Peak rearfoot inversion moment and work were significantly reduced (P = 0.045 and P < 0.001, respectively) in the inverted orthotic condition suggesting a decreased demand on the soft tissue structures that control eversion. Significant differences were seen in tibial rotation (P = 0.043), knee adduction (P = 0.035), and knee abduction moment (P < 0.001) in the inverted orthotic condition, suggesting alterations were made further up the kinetic chain. CONCLUSIONS: The differences in kinetic parameters at the rearfoot may result in fewer injuries of the rearfoot soft tissue structures when using inverted orthotics. These alterations in lower-extremity mechanics associated with inverted orthoses provide clinicians some evidence for prescribing this device.